Peripheral polyneuropathy in severely obese patients with metabolic syndrome but without diabetes: Association with low HDL-cholesterol - Nienov,Otto Henrique (2017)
Summary Introduction: The purpose of this study was to evaluate the prevalence of peripheral polyneuropathy (PPN) in subjects with grade II and III obesity (Ob-II,III) and metabolic syndrome (MetS) but without diabetes and to investigate possible associated factors. Method: A cross-sectional study was performed in non-diabetic Ob-II,III,MetS patients using the Michigan Neuropathy Screening Instrument (MNSI) to assess the presence of PPN. Results: A total of 24 of 218 non-diabetic Ob-II,III,MetS patients had PPN. Based on univariate analysis, serum levels of LDL-cholesterol (p=0.046) were significantly associated with PPN, while serum triglycerides (p=0.118) and low HDL-cholesterol (p=0.057) showed a tendency toward this association. On a Poisson regression analysis, when the three possible associations were included, low HDL-cholesterol (p=0.047) remained independently associated. Conclusion: In non-diabetic Ob-II,III,MetS patients, PPN defined by the MNSI showed a high prevalence and was associated with low levels of HDL-cholesterol. In order to diagnose that complication, neurological evaluation should be performed in these patients.